Removal of Intrathoracic Porcupine (Coendou sp.) Quill in one Bitch with Pyothorax by Thoracoscopic Surgery - da Silva Reinstein, Rainer; Caye, Pâmela; Nascimento Antunes, Bernardo; Ferreira da Rosa, Eliza; Segura Engelsdorff, João; Vanessa Vaccarin, Charline; Curvello de Mendonça Müller, Daniel; Veloso Brun, Maurício (Acta Scientiae Veterinariae, 2024)
Background: Accidents involving porcupines (Coendou sp.) occur in rural areas or in locations of preserved forests in various regions of Brazil. In addition to their fur, they have very strong, horn-like quills that penetrate the skin of their assailant when attacked. Video-assisted surgery of the thoracic cavity or thoracoscopy is a crucial tool for treating pleural effusion and for evaluating and treating intrathoracic trauma in small animals. This study reports the case of a dog with an intrathoracic infection of unknown origin, wherein a porcupine quill was found adhered to the mediastinum during thoracoscopy and removed using Crile forceps. Case: A 4-year-old bitch of a non-specific breed, weighing 15 kg and having no prior history of trauma, was treated for dyspnea symptoms present for 7 days. The dog had previously been treated and prescribed antimicrobial therapy; however, the symptoms returned after treatment completion. Complementary imaging tests revealed a large amount of pleural effusion, particularly evident in the left hemithorax, which was drained and analyzed; the findings indicated septic exudate. The dog was taken to the operating room for an exploratory thoracoscopy procedure. During the procedure, an 11-mm port was positioned in the 8th left intercostal space at the level of the costochondral joint. Another 11-mm port was positioned in the paraxiphoid region using a 10-mm, 30° scope. The scope was then repositioned at the second port, allowing for inspection, biopsy sample collection, and washing and draining of the cavity, which revealed pleuritis and deposits of reddish fibrinoid tissue with flaky white spots, suggestive of bacterial infection. During the final inspection, a dark, pointed structure adhering to the mediastinum was identified and removed using a curved Crile hemostatic forceps. A chest drain was positioned in the paraxiphoid access wound after being routed through a subcutaneous tunnel. Following this, the access wounds were sutured, and negative pressure was reestablished. Immediately after the procedure and removal of the foreign body, antibacterial treatment was started, and the dog returned to a healthy condition. The histopathological report of the pointed structure was consistent with a hystrix-like hair (porcupine quill). Discussion: The patient’s recovery was better with surgical intervention through thoracoscopy than with exploratory thoracotomy. These results align with the international literature, which acknowledges that minimally invasive surgery significantly reduces the postoperative pain, recovery time, and duration of hospitalization. Furthermore, video assistance played a crucial role in locating and assisting in the foreign body removal, primarily due to the magnification of the image by the endoscope. Accidents involving dogs and porcupines constitute a small fraction of cases in veterinary medical care. This is because most pet owners seek veterinary care only when the animal is struck by many quills or some complication arises. It is crucial to conduct a thorough investigation in such cases to ensure that all the quills are found and removed, considering their potential to migrate, which could lead to severe complications if not addressed. Thus, it was evident that the thoracoscopy procedure facilitated a rapid recovery for the patient by allowing accurate localization and removal of the foreign body that caused the infection. Keywords: dog, surgery, quill, videosurgery, video-assisted thoracoscopic, VATS. Título: Remoção de espinho de ouriço (Coendou sp.) intratorácico em uma cadela com piotórax por toracoscopia Descritores: cão, cirurgia, espinho, videocirurgia, cirurgia torácica videoassistida, CTVA.